2020
DOI: 10.3803/enm.2020.35.2.435
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Risk Scoring System Derived from Meta-Analyses of Papillary Thyroid Cancer

Abstract: Background: The aim of this study was to develop a scoring system to stratify the risk of papillary thyroid cancer (PTC) and to select the proper management. Methods: We performed a systematic search of MEDLINE and Embase. Data regarding patients' prognoses were obtained from the included studies. Odds ratios (ORs) with statistical significance were extracted from the publications. To generate a risk scoring system (RSS), ORs were summed (RSS1), and summed after natural-logarithmic transformation (RSS2). RSS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…N1b LN metastasis has been further recognized as a predictive factor for recurrence [ 33 ]. A meta-analysis suggested that a tumor size over 2 cm (OR 2.69, 95% CI 2.06–3.50) and LN metastasis (OR 3.24, 95% CI 2.61–4.02) were predictive factors for recurrence [ 34 ]. Wang et al demonstrated that male sex, tumor size, and LN metastasis were associated with tumor recurrence of PTC in their large, multicenter study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…N1b LN metastasis has been further recognized as a predictive factor for recurrence [ 33 ]. A meta-analysis suggested that a tumor size over 2 cm (OR 2.69, 95% CI 2.06–3.50) and LN metastasis (OR 3.24, 95% CI 2.61–4.02) were predictive factors for recurrence [ 34 ]. Wang et al demonstrated that male sex, tumor size, and LN metastasis were associated with tumor recurrence of PTC in their large, multicenter study [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ∼10-30% of DTC patients develop metastatic or recurrent diseases, among whom 33-50% eventually progress into radioiodine-refractory (RAI-R) diseases (1,2). The identification of predictors of clinical outcomes for DTC patients is of immense clinical value (3,4). 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT), combining functional and anatomic information, has become a valuable tool for the staging, treatment response assessment, prognosis prediction, and surveillance of patients with various malignancies (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, ~10–30% of DTC patients develop metastatic or recurrent diseases, among whom 33–50% eventually progress into radioiodine-refractory (RAI-R) diseases ( 1 , 2 ). The identification of predictors of clinical outcomes for DTC patients is of immense clinical value ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%